An Overview of the Noise Levels Measured in Industrial Facilities in Serbia and Implemented Methods of Protection - LUBURIĆ, Uranija Kozmidis; SAMARDŽIĆ, Selena Dušan; LAKATOŠ, Robert; MIHAILOVIĆ, Aleksandra; VESELINOVIĆ, Milka (Archives of Acoustics, 2020)
Noise is one of the most significant factors which not only disturbs working conditions, but has a large impact on workers’ health. This problem has existed in industries since the beginning and, despite technical and other solutions, it has not been solved. There is a large number of papers, supported with very detailed analyses, that investigate noise levels in industry or contain questionnaires about the impact of noise on workers’ overall health and work abilities. The purpose of this paper is to contribute to the global picture of sustainability and the development of strategies for improving the quality of working environment, with special attention to the generation of noise in different production processes in thirteen different industries in Novi Sad, Serbia. The paper also seeks to examine the advantages and drawbacks of the implemented protective methods and to provide some recommendations for their better implementation in order to contribute to solving this significant problem of today.